ANALISIS RISIKO USAHATANI BAWANG MERAH DI KECAMATAN PRINGSEWU KABUPATEN PRINGSEWU - Nurfaizah, Trya Lulu; Rosanti, Novi; Suryani, Ani (Lampung University, 2025)
This study examines the risk, the risk mapping, and the risk mitigation techniques at shallot farming. . The study was carried out in Pringsewu District, Pringsewu Regency from January to February 2025. Saturated sampling was employed as the method for sampling. There were 59 shallot farmer respondents in this survey, consisted of 23 farmers from Fajar Agung Village, 14 farmers from Podomoro Village, 14 farmers from Pajaresuk Village, and 8 farmers from South Pringsewu Village. This study utilised various approaches including the risk mapping, variation coefficient analysis, cost structure analysis, R/C income analysis, and descriptive analysis of risk mitigation strategies. The study finds that (1) The level of risk production is 0.14, which considers as low risk; the level of pricing risk is 0.39, which falls into low in category; and the level of income risk is 0.82, and it considers as high risk. (2) Risk mapping reveals that the disease attacks tthe shallot primary cause the severe risk. (3 ) Various risk management strategies conducts by farmers are including the use of pesticides, choosing superior shallot seeds that are resistant to plant pests, controlling planting schedules, and eliminatign the infected plants. . Key words: cost structure, income, mapping, risk, strategies